Determining the Nearshore Wave Climate between Galinhos and Guamaré – Brazil - Scudelari, A. C. (2011)
This paper applies two numerical models, REFDIF and SWAN, to characterize the wave climate near the coastal stretch between Galinhos and Guamaré, Brazil. This region is exposed both to incoming swell from North Atlantic Ocean and to local seas generated by steady SE Trade Winds, tidal currents are strong, and beach morphology is very dynamic. Both models were applied to the propagation of different wave conditions, from offshore to the coastline of Galinhos-Guamaré. The following incident wave conditions were considered: periods between T=5 s and 13 s, deep water heights between H=0.8 m and 2.4 m, and off-shore directions between N-60- W (60º) and N-60-E (60º). A total of 1053 simulations were performed for the incident wave conditions for each model. The results consist on the wave heights and wave directions of study area. It is also analyzed the results at points over the bathymetric line of -8 m (CD). A comparative analysis of the results obtained with each model permit to assess their suitability for this area and evaluate their limitations and potentialities